UV Index for Public Health Awareness Based on OMI/NASA Satellite Data at King Abdulaziz University, Saudi Arabia - Abdullah Addas; Mahmoud Ragab; Ahmad Maghrabi; S. M. Abo-Dahab; Eman F. El-Nobi (Advances in Mathematical Physics)
Exposure to ultraviolet radiation (UV) is essential for good health and formation of vitamin D while overexposure poses a risk to public health. Therefore, it is important to provide information to the public about the level of solar UV radiation. The ultraviolet index (UVI) is used to help avoid the negative effects of ultraviolet (UV) radiation on humans and to optimize individual exposure. There is limited ground measurement of solar UV radiation, but satellite Ozone Monitoring Instrument (OMIs) satellite products with a spatial resolution of 1°×1° can be used to create UV index climatology at local noon time. In this study, we utilize OMI satellite products collected over the campus of King Abdulaziz University (KAU) (21.5° North and 39.1° East), Jeddah, Saudi Arabia, to estimate changes in exposure to UV over a period of 15 years (2004-2020). The results indicate a significantly increasing trend in UV index over this period. Between 2004 and 2020, daily “extreme” UV (UVI>11, as defined by the World Health Organization (WHO)) occurred on 46.60% of days. The frequency of low UVI (UVI<2) was only about 0.06%. These results imply dangerous exposure levels to solar UV radiation on the KAU campus and call for safety measures to increase awareness and decrease direct exposure; for example, by implementing the United States Environmental Protection Agency (EPA) general guidelines.